Khotbah Humoris dari Perspektif Homiletika - Solibut, Elto (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
Humour is commonly used in sermons. There are even preachers who are famous for always bringing fresh humour to their sermons. But is humour in line with the principles of homiletics? This research explores the idea of humorous preaching from a homiletic perspective. The method used is a literature study. As a result, the author found that humour positively impacts sermons because it can help the preacher creatively present teachings that attract attention and are easy for listeners to understand. However, on the other hand, excessive or misplaced use of humour can have negative impacts, including underestimating and weakening the spirit of the sermon, lack of assertiveness, being biased, changing form, and other adverse effects.